Re-Imagining Localism and Food Justice: Co-Op Cincy and the Union Cooperative Movement - Zoller, Heather M. (Frontiers in Communication, 2021)
Co-op Cincy is an incubator of worker- and community-owned cooperatives, including farm and food hub Our Harvest. The incubator is part of the innovative 1worker1vote.org network of unionized worker cooperatives stemming from a partnership between the Spanish Mondragon Cooperatives and the U.S. Steelworkers. This Community Case Study examines Co-Op Cincy’s food sector organizing as an example of resistance to the industrial, corporate food system. Their hybrid and experimental approach creatively re-imagines both cooperative ownership and localist food systems. Whereas some local efforts fail to address questions of social justice or drift from social justice missions, this essay describes how Co-Op Cincy and Our Harvest 1) define their social justice goals in pursuit of locally rooted ownership, 2) raise consciousness about the connections among food systems and racial and class disparities as well as the need for sustainability, solidarity, and democratic ownership, and 3) embody these commitments in everyday organizing. Their experimentation lends insights into potential paths to create a more equitable food system and a more just economy.